PELATIHAN PENULISAN DAN PUBLIKASI KARYA ILMIAH BAGI GURU SMA NEG. 1 PAKUE, KOLAKA UTARA - Hasria Alang; Hastuti Hastuti; Muh. Sri Yusal; Ibnu Mansyur Hamdani (Jurnal Abdimas Bina Bangsa, 2021)
Scientific writing (KTI) is a writing that contains ideas or ideas and is compiled based on facts. Scientific writing is a must that must be owned by a teacher, especially when proposing a class promotion. Based on the results of observations, it is known that the teachers of SMA Neg. 1 Pakue has not been able to compile KTI and always relies on the services of others to make KTI when needed. This is what motivated the service team to conduct KTI writing training at that place. This training uses lecture, brainstorming and training methods to achieve the expected target. The results of the activity show that this training can improve the understanding, knowledge and experience of the service participants